The EU-Ukraine trade liberalization: How much do the costs of tariff elimination matter? - Miriam Frey; Zoryana Olekseyuk (FIW - Research Centre International Economics, 2013)
The establishment of the currently negotiated Free Trade Agreement (FTA) between EU and Ukraine is the next significant step towards Ukraine's deeper integration into the world economy, widely expected to result in additional welfare gains. As developing countries face some costs associated with trade liberalization, this paper contributes to the literature by analyzing the effects of the EU-Ukraine FTA taking into account the loss of tariff revenues as well as the changed economic conditions after Ukraine's accession to the WTO in 2008. In particular, we calculate the effects of a unilateral tariff elimination in a Computable General Equilibrium (CGE) model for Ukraine simulating three scenarios reflecting different means to compensate for the loss in tariff revenues. It turns out to be important to take these costs into consideration while modeling trade liberalization, as the results vary significantly across the scenarios. In general, we find that tariff elimination has only a small impact on the country's welfare because of the already strongly reduced tariff rates after Ukraine's WTO accession. The effects can even be negative if the country tries to refinance the trade liberalization costs by means of tax policy. According to our simulations the most welfare enhancing option would be the provision of financial support by the EU, which is in fact suggested in the latest European Parliament resolution.
Keywords: C68; F13; F15; H50; O52; 330; Ukraine; EU; Trade; Integration; CGE; Public Spending